Positivisasi Hukum Islam dan Persinggungannya dengan Kelompok Etnonasionalis di Aceh - Nyak Fadlullah (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2020)
Abstract: This paper aims to examine the discourse of positivization of Islamic Law in post-conflict settings and its relation to ethnonationalist groups in Aceh. This qualitative research uses a socio-legal-historical approach and content analysis as a dimension of analysis. The research was carried out by observation, interview and documentation. The results showed that the existence of Islamic law in Aceh did not occur monotonously, since there were many influences behind its development. The relationship between the three main areas, namely sharia, state law, and customs, greatly affects the existence of Islamic law in Aceh. The positivization of Islamic law in Aceh in the form of qanūns was born out of the articulation process between the three main domains. This articulation means having a clear connection between the three areas, with an important note that Islamic law is not born from the legislative process alone as a given, but is more of a struggle in nature which in this case is always intertwined with the local political situation vis a vis national politics. Furthermore, the involvement of ethnonationalism groups in the post-conflict discourse on the positivization of Islamic law is an implication of the transformation of the Free Aceh Movement (GAM) into the government bureaucracy in both the executive and legislative domains. Abstrak: Tulisan ini bertujuan melihat eksistensi wacana positivisasi hukum Islam pascakonflik dan kaitannya dengan kelompok etnonasionalis di Aceh. Penelitian menggunakan pendekatan sosio-legal-historis dengan analisis isi. Teknik pengumpulan data dilakukan dengan wawancara, observasi dan dokumentasi. Hasil penelitian menunjukkan bahwa eksistensi syariat Islam di Aceh tidak terjadi secara monoton, banyak pengaruh di balik perkembangannya. Hubungan antara tiga wilayah utama, yakni syari’ah, hukum negara, dan adat-istiadat sangat mempengaruhi keberadaan dan eksistensi hukum Islam di Aceh. Positivisasi hukum Islam di Aceh dalam bentuk qanūn lahir karena proses artikulasi antara tiga domain utama tersebut. Artikulasi ini bermakna memiliki sambungan yang jelas di antara tiga wilayah tersebut, dengan catatan penting bahwa syari’at Islam tidak lahir dari proses legislasi saja sebagai sebuah given, tetapi lebih bersifat perjuangan yang dalam hal ini selalu berkait kelindan dengan situasi politik lokal yang berhadapan (vis a vis) dengan politik nasional. Sementara keterlibatan kelompok etnonasionalisme dalam wacana positivisasi hukum Islam di Aceh pascakonflik merupakan implikasi dari hasil transformasi Gerakan Aceh Merdeka (GAM) ke dalam birokrasi pemerintahan, baik dalam domain eksekutif maupun legislatif.